High Expression of VAV Gene Family Predicts Poor Prognosis of Acute Myeloid Leukemia. (December 2021) - Mu, Dan; Long, Sili; Guo, Ling; Liu, Wenjun
Objectives: VAV family genes ( VAV1, VAV2, and VAV3 ) are associated with prognosis in various cancers; however, they have not been evaluated in acute myeloid leukemia (AML). In this study, the prognostic value of VAV expression in AML was evaluated by a single-center study in combination with bioinformatics analyses.Methods: The expression and prognostic value of VAVs in patients with AML were investigated using various databases, including GEPIA, CCLE, EMBL-EBI, UALCAN, cBioPortal, STRING, and DAVID. Blood samples from 35 patients with AML (non-M3 subtype) and 13 benigh individuals were collected at our center. VAV expression levels were detected by real-time quantitative PCR (RT-qPCR) and western blotting. Clinical data were derived from medical records.Results: Based on data from multiple databases, the expression levels of VAV1, VAV2, and VAV3 were significantly higher in AML than in control tissues ( P < 0.05). RT-qPCR and western blotting results showed that VAV expression in mRNA and protein levels were higher in patients with AML that in the control group ( P < 0.05). Complete remission rates were lower and risks were higher in patients with AML with high VAV1 expression than with low VAV1 expression ( P < 0.05). High levels of VAV2, VAV3, and VAV1 were related to a poor overall survival, and this relationship was significant for VAV1 ( P < 0.05). High expression levels of genes correlated with VAV1, such as SIPA1, SH2D3C, and HMHA1 were also related to a poor prognosis in AML. Functional and pathways enrichment analyses indicated that the contribution of the VAV family to AML may be mediated by the NF-κB, cAMP, and other pathways.Conclusion: VAVs were highly expressed in AML. In particular, VAV1 has prognostic value and is a promising therapeutic target for AML.